A review of the repair of reinforced concrete beams - Jumaat, Mohd Zamin; Kabir, M.H.; Obaydullah, M. (Journal of Applied Science Research, 2006)
This paper reviews works on repairing of deteriorated reinforced concrete beams. Every structural element should be designed for a particular type of loading as well as for adopting of different types of environment. However many civil structural elements, like reinforced concrete beams are often required to be repaired to restore the structural integrity and to protect the reinforcement from sever weathering condition. Recently repairing is gradually increasing with the increase of age of concrete structures. In some instances it may be more economical to accept the need for maintenance or repair at suitable intervals than to attempt to build a structure that will be maintenance-free under severe conditions for a long period. Several types of materials and techniques are available for repairing of exiting deteriorated reinforced concrete beams. In this paper, causes of deterioration of concrete as well as repairing by using cement grout, mortar, concrete, sprayed concrete or shotcrete, epoxy, ferrocement with mortar, Fiber Reinforced Polymer (FRP) Sprayed Fiber Reinforced Polymer (SFRP) and the techniques of applying of these materials and also some resin based materials for bonding agent between interface of old concrete and newconcrete are reported.The advantages anddisadvantages ofthesematerials,causes ofdebondingbetweenconcretesubstrateandnewconcreteapplied on substrate and preventive measures are also discussed.